Influence of the amount of dentifrice and fluoride concentrations on salivary fluoride levels in children - Hall, Kevin Bruce [UNESP]; Delbem, Alberto Carlos Botazzo [UNESP]; Nagata, Mariana Emi [UNESP]; Hosida, Thayse Yumi [UNESP]; De Moraes, Felipe Ricardo Nunes [UNESP]; Danelon, Marcelle [UNESP]; Cunha, Robson Frederico [UNESP]; Pessan, Juliano Pelim [UNESP] (My University, 2016)
Purpose: This study evaluated fluoride (F) concentrations in saliva of children after brushing with dentifrices containing different F concentrations (zero, 550, and 1,100 ppm F) in different quantities (full bristles, transversal technique, and pea-sized). Methods: Eight- to 10-year-old volunteers (n=24) were randomly assigned into nine experimental groups (dentifrice type versus amounts) following a double-blind, crossover protocol. After a one-week washout period (use of placebo toothpaste), stimulated saliva was collected prior to toothbrushing (baseline) and at five, 15, 30, 60, and 120 minutes after toothbrushing with one of the possible combinations. Centrifuged saliva was used for F analysis after buffering with TISAB III. Data were submitted to repeated-measures ANOVA followed by Student-Newman-Keuls' test (P<0.05). Results: Salivary F peaked at five minutes after brushing, decreasing exponentially afterward. A clear dose-response relationship was seen between F concentration/amount of dentifrice applied and the mean area under the curve (AUC) of salivary F concentrations (P<0.001). The low-fluoride toothpaste applied using transversal technique or full bristles led to a significantly higher AUC than the conventional toothpaste using a pea-sized amount. Conclusions: Brushing with a low-fluoride toothpaste applied using the transversal technique delivers more fluoride to saliva compared to a conventional toothpaste in a pea-sized amount.
Keywords: Children; Dentifrice; Fluorides; Saliva